Asupan energi dan status gizi peserta didik - Paendong, Nikita Ester; Punuh, Maureen Irinne; Musa, Ester Candrawati (Holistik Jurnal Kesehatan, 2025)
Background: Adolescence is a crucial life period in human development marked by significant biological, emotional, social, and cognitive changes as individuals transition from childhood to adulthood. Meeting nutritional needs during adolescence is absolutely essential. Deficiencies in energy and other nutrients can have negative effects that persist into adulthood. Both under nutrition and overnutrition often stem from imbalanced energy intake. Most Indonesians still have unstable energy intake, often exceeding the recommended dietary allowance, even though many adolescents in Indonesia have normal nutritional status. Purpose: To analyze the relationship between energy intake and nutritional status among students. Method: This study used a quantitative, analytical observational design with a cross-sectional approach. The sample consisted of 77 seventh and eighth-grade students selected through total sampling (entire population). The variables examined were energy intake and nutritional status. Energy intake data were collected using a 24-hour food recall form, while nutritional status was assessed using BMI-for-age (BMI/U) through anthropometric measurements, including height (measured using a SECA microtoise) and weight (measured using a SECA digital scale). The relationship between variables was analyzed using Spearman’s Rank Correlation test. Results: The results showed that the respondents' nutritional status was dominated by good nutritional status (75.3%), and normal energy intake (51.9%). A Spearman's Rank Correlation test showed a relationship between energy intake and nutritional status (p = 0.000; r = 0.388). Conclusion: That most respondents had good nutritional status and normal energy intake. There was a relationship between energy intake and nutritional status, with a positive r value indicating a unidirectional relationship. Suggestion: Future researchers can use these results as a reference but should add other methods or variables that were not included in this study.   Keywords: Adolescents; Energy Intake; Nutritional Status.   Pendahuluan: Masa remaja adalah fase krusial dalam hidup manusia yang ditandai dengan transformasi signifikan pada aspek biologis, emosional, sosial, dan kognitif selama transisi dari anak-anak ke dewasa. Status gizi yang kurang maupun lebih, sering kali berakar dari asupan energi yang tidak seimbang. Sebagian besar masyarakat Indonesia memiliki asupan energi yang masih tidak stabil dan melebihi angka kecukupan energi meskipun sebagian besar remaja di Indonesia memiliki status gizi normal. Tujuan: Untuk menganalisis hubungan antara asupan energi dengan status gizi pada peserta didik. Metode: Jenis penelitian ini adalah penelitian kuantitatif yang bersifat observasional analitik dengan menggunakan desain atau rancangan penelitian yang dipakai yaitu studi potong lintang dengan sampel 77 siswa kelas VII-VIII yang dipilih secara total sampling/total populasi. Variabel dalam penelitian ini yaitu asupan energi dan status gizi. Data asupan energi dikumpulkan melalui formulir food recall 24 jam dan status gizi diukur dengan IMT/U melalui pengukuran antropometri terlebih dahulu menggunakan alat ukur tinggi badan dan berat badan yaitu mikrotoise dan timbangan digital merk SECA. Analisis hubungan menggunakan uji Spearman’s Rank Correlation. Hasil: Status gizi didominasi oleh status gizi baik (75.3%), asupan energi normal (51.9%), dan didapatkan adanya hubungan antara asupan energi dengan status gizi berdasarkan hasil uji Spearman’s Rank Correlation dengan nilai (p= 0.000; r = 0.388). Simpulan: Sebagian besar responden memiliki status gizi baik dan asupan energi normal, serta adanya hubungan antara asupan energi dengan status gizi dengan arah hubungan nilai r positif menunjukkan hubungan searah. Saran: Bagi peneliti selanjutnya dapat menggunakan hasil ini sebagai referensi, namun dengan menambah metode lain atau dengan menambahkan variabel yang belum ada pada penelitian ini.   Kata Kunci: Asupan Energi; Remaja; Status Gizi.